GEOMECHANICS EVALUATION IN PORE PRESSURE ESTIMATION AND ABNORMAL PRESSURE IDENTIFICATION: CORRECTION AND MODIFICATION OF THE EATON METHOD ON FORMATION IN XX FIELD - Karisma Prameswari, Ghaniy
Geomechanical evaluation, particularly in pore pressure estimation, is crucial in oil and gas drilling. Accurate estimation of pore pressure is necessary for planning and optimizing drilling processes to reduce the risk of failure and errors, thereby minimizing costs. The Eaton equation is a commonly used equation for pore pressure estimation. However, this equation is based on drilling data from formations in the Gulf of Mexico, where the formations are predominantly composed of carbonate and clay with a constant pressure gradient. This indicates that the same method may not always be applicable in all fields and adjustments are required. Therefore, modifications to the Eaton equation are necessary by introducing scaling factors and constants to adapt it to the specific field conditions being studied and to generate a corrected pore pressure model. This study includes a literature review, data collection, correction of drilling parameter data, D-exponent calculations, pore pressure estimation using the modified Eaton method, and identification of abnormal pressure zones. The data used in this study are from two wells, namely well-X3 and well-X5 in XX field of Sumatera. The results of this study provide profiles of overburden pressure, pore pressure, and depth intervals with abnormal pressure. The findings of this study can serve as recommendations and guidelines for future well drilling, enabling better preparation in terms of planning, design, optimization, and problem mitigation.